Soft Spiral‐Shaped Microswimmers for Autonomous Swimming Control by Detecting Surrounding Environments. (21st September 2020) - Yoshida, Koki; Onoe, Hiroaki
Abstract : Microswimmers In article number 2000095, Hiroaki Onoe and Koki Yoshida achieve the fabrication of soft spiral‐shaped microswimmers that can sense the external temperature and deform their spiral‐shaped body in order to change propulsion velocity, similar to living organisms. The proposed microswimmers can open new avenues for various microscale biochemical applications such as autonomous soft‐robots and soft micro‐probes.